Lahore pregnancy cohort study; association of maternal nutritional status, environmental factors and psychological status with neonatal anthropometric data and pregnancy outcomes among Pakistani pregnant women - Ashraf, Shazia (2024)
In Pakistan, prevalence of maternal mortality rates is on higher side than in other developing countries. The Lahore Pregnancy Cohort Study is a comprehensive investigation designed to explore the intricate relationship between maternal nutritional status, environmental factors, psychological factors, and their impact on neonatal anthropometric data and pregnancy outcomes among pregnant women and neonate’s health in Pakistan. The LPCS was a two-year prospective cohort study started in 2019 that recruits Pakistani pregnant women from Fatima Memorial Hospital Lahore, Pakistan through convenient sampling technique. Participants of the study (approximately 227) between the age of 19-40 years were interviewed in three intervals. (2nd, 3rd trimester and postpartum). The mother’s information was collected from the hospital records and via a self-structured questionnaire. With a focus on the Pakistani population, this comprehensive study data on maternal nutritional status, encompassing dietary habits, and body mass index (BMI). Environmental factors, such as socioeconomic status, food insecurity, are also assessed to determine their potential influence on pregnancy outcomes. The psychological status of pregnant women is evaluated, including stress, anxiety and depression. Pregnancy outcomes such as gestational weight gain (GWG), gestational diabetes mellitus (GDM) and anemia. Furthermore, it investigated factors linked to infant’s birth outcomes, such as birth length, weight, head circumference, abdominal circumference and APGAR score. Significant findings highlighted that mostly respondent is food secured (100 %) and mild depression is observed among the mothers. Socio-demographic, socio-economic and dietary variables are associated with the prevalence of anemia. There exists a significant difference between the prevalence of anemia at different points in pregnancy and post-partum with mean Hb levels of 11.61 ± 1.05 (2nd trimester), 11.11 ± 1.62 (3rd trimester) and 10.41 ± 1.56 (post-partum). Mean score comparison showed that fasting and random blood glucose were also significantly different at different time points among study respondents (p < 0.05). Insufficient consumption of dietary intake is observed, with a higher reliance on supplements (p < 0.01) to meet their nutritional needs. In addition, dietary adequacy was found to be related with anthropometric measurements with different food item effecting differently. Moreover, 44.9% newborns were female while 55.1% were male with 18.5% of neonates having lower birth weight. The study underscored the positive effects of environmental factors and psychological health. In conclusion, this study highlighted key issues related to maternal and infant health in Lahore. The findings from this study hold the potential to inform public health initiatives, healthcare policies, and interventions aimed at improving maternal and neonatal health in Pakistan. Ultimately, the goal is to contribute to the enhancement of prenatal care and the overall well-being of expectant mothers and their offspring in this region.